Research of public infrastructure system and security policy in cyberspace - Jie QIU; Rui HAN; Zhifeng WEI; Zhiyang WANG (网络与信息安全学报)
Considering the key elements, such as object, resources, activities, and other equipment, as same as system, data, environmental and other aspects of demand, the public infrastructure system and security policy between physical space and cyberspace were taken as a basic point.A scientific system of public infrastructure in cyberspace was constructed.From the perspective of dual authentication of management authentication and application authentication, some corresponding safety policies and implementation suggestions were given from the aspects of user/device management and identity authentication.